The Effect of a Self-Management Intervention on Reducing TikTok Addiction Behavior among Students - Kenechukwu Chinenye Osakwe; Benedicta Ndidi Agu (International Journal of Counseling and Psychotherapy, 2026)
Background: The increasing use of social media platforms, particularly TikTok, among adolescents has raised concerns regarding excessive engagement and its impact on academic performance and daily functioning. Objective: This study aims to examine the effectiveness of self-management techniques implemented through group counseling in reducing TikTok addiction behaviour among students. Method: A mixed-method approach with a sequential explanatory design was employed. The study was conducted in 2025 at Oru West LGA, Imo State, involving 15 students selected through simple random sampling. Data were collected using questionnaires, interviews, observation, and documentation. Quantitative data were analysed using a paired sample t-test, while qualitative data were used to support the interpretation of behavioural changes. Result: The findings indicated a significant reduction in TikTok addiction levels, as evidenced by lower posttest scores compared to pretest results (p < 0.05). Qualitative findings also revealed increased self-awareness and improved self-regulation among participants. Conclusion: Self-management techniques delivered through group counseling are effective in reducing maladaptive digital behaviour. Contribution: This study contributes empirical evidence supporting the integration of self-management strategies into school counseling programs to address social media addiction among adolescents.